Studi Literatur Analisis Perkembangan Beton Geopolimer Berbasis Fly Ash terhadap Kekuatan dan Durabilitas Beton - Jonathan, Henry; Kristianto, Anang (Universitas Kristen Maranatha, 2025)
Geopolymer concrete is a type of concrete that utilizes waste materials as a substitute for Portland cement. One of the most commonly used waste materials in geopolymer concrete is class F fly ash. Based on experimental research, class F fly ash has the potential to act as a binding material in geopolymer concrete mixtures. Several studies have indicated a significant relationship between class F fly ash and the strength and durability of geopolymer concrete. However, other studies have not supported this statement. To address this issue, a literature review was conducted to examine the performance of fly ash-based geopolymer concrete in terms of strength and durability. The data used in this study were derived from 25 research journals, comprising a total of 126 specimens. These specimens were categorized based on the results of strength and durability tests. Strength was evaluated using compressive strength tests, while durability was assessed through water absorption, exposure to elevated temperatures, and exposure to chemical substances. The study focused on analyzing the effect of fly ash percentages on the strength and durability of geopolymer concrete. The analysis methods applied in this study included visual graphics and regression statistics. Based on the findings of the collected data, it was concluded that fly ash, as a precursor, does not have a significant effect on either the strength or durability of geopolymer concrete.